2007
DOI: 10.1021/jp066080w
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Ice Nucleation Rate Coefficient of Water Droplets Coated by a Nonadecanol Monolayer

Abstract: The heterogeneous ice nucleation rate coefficient (j het) of water droplets coated with a monolayer of 1-nonadecanol was determined from multiple freezing/melting cycles. Freezing was monitored optically with a microscope for droplet radii between 31 and 48 μm and with a differential scanning calorimeter for radii between 320 and 1100 μm. The combination of these two techniques allows the surface area of the 1-nonadecanol nucleating agent to be varied by more than a factor of 1000, showing that j het increases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

26
421
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 235 publications
(448 citation statements)
references
References 26 publications
26
421
1
Order By: Relevance
“…Subcritical ice clusters may be produced at a high rate but are prevented from reaching a critical size by the confinement in the pores. Marcolli (2014) showed that the CNT-based parameterization by Zobrist et al (2007) is able to describe the observed melting point depression in pores as a function of temperature and should therefore be well suited to estimate critical embryo sizes. The critical embryo volume for homogeneous ice nucleation predicted by this parameterization is 109 nm 3 at 254 K and increases to 1441 nm 3 at 265 K. We therefore consider the energy barrier and critical embryo size predicted by CNT as a quantity with a physical basis.…”
Section: Classical Nucleation Theorymentioning
confidence: 99%
See 4 more Smart Citations
“…Subcritical ice clusters may be produced at a high rate but are prevented from reaching a critical size by the confinement in the pores. Marcolli (2014) showed that the CNT-based parameterization by Zobrist et al (2007) is able to describe the observed melting point depression in pores as a function of temperature and should therefore be well suited to estimate critical embryo sizes. The critical embryo volume for homogeneous ice nucleation predicted by this parameterization is 109 nm 3 at 254 K and increases to 1441 nm 3 at 265 K. We therefore consider the energy barrier and critical embryo size predicted by CNT as a quantity with a physical basis.…”
Section: Classical Nucleation Theorymentioning
confidence: 99%
“…Several parameterizations of j hom (T ) have been proposed in the literature. Three different parameterizations are considered in this study to evaluate the measured data, namely the parameterization provided by Zobrist et al (2007), hereafter referred to as Z07, the parameterization given by Pruppacher and Klett (1997), P&K97, and the parameterization from Ickes et al (2015), Ick15. Differences between these parameterizations are discussed by Ickes et al (2015) and concern mainly the treatment of F diff (T ), σ (T ), and n s .…”
Section: Classical Nucleation Theorymentioning
confidence: 99%
See 3 more Smart Citations